Ethnosains: Analisis Implementasi Budaya Melayu Riau pada Pembelajaran Di Sekolah Dasar: Ethnosains: Analisis Implementasi Budaya Melayu Riau pada Pembelajaran Di Sekolah Dasar - Vany Sinthya; Syelvina Safitri; Suripah (Perspektif Pendidikan dan Keguruan, 2023)
The objective of this study was to analyze the implementation of social attitudes consist of honesty, discipline, responsibility, and tolerance in the elementary schools of Karanganyar Regency, Indonesia. The method used in this study was descriptive qualitative with a case study design. Eight informants were recruited consist of teachers as well as students. The techniques that were used in this study were observation and interview. The data analyzed by data reduction, data presentation, and conclusion drawing. The assessment techniques to check data validity were technical triangulation and source triangulation. The results of this study showed that (1) Most teachers did not observe yet their students inside and outside class activity every day. (2) Some teachers take notes every day, some others incidentally. The indicators got from a combination of official guideline and their own. (3) All teachers at least asses two dimensions (discipline and honesty), the others wholly ignored. All teachers at least use two techniques. (4) The teachers follow up on the assessment by informs students periodically (quarterly) and give them praise or advice. The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to social attitude assessment. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations